2017
DOI: 10.1002/pa.1669
|View full text |Cite
|
Sign up to set email alerts
|

Public caseworkers' strategies coping with accountability demands

Abstract: Public employees are required to manage multiple accountability requirements by investing in the relationship with those who demand accountability, making a commitment to the given tasks and anticipating what might happen. The purpose of the study is to explore how social caseworkers manage multiple accountability requirements compared to public managers. The analysis from child welfare caseworkers' interview data highlights a number of ways on how social caseworkers respond to multiple accountabilities. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…In a study of non-executive boards, for instance, Roberts et al (2005, p. S16) found that some boards helped executives to “make as full a use as possible of the different views and experiences” leading to better decisions. In a very different study focusing on case workers, Hwang and Han (2017) found that accountability pressures had a positive effect on cognitive dimensions, such as “talk,” “discussion,” and “gathering of more information” (see also Belardinelli et al, 2018; Kogan, 2017). Interestingly, recent studies also relate integrative decision-making by managers to the “negativity bias” in their strategic environment, stimulating improved decisions (Holm, 2018; Nielsen & Moynihan, 2017).…”
Section: Information Processingmentioning
confidence: 99%
“…In a study of non-executive boards, for instance, Roberts et al (2005, p. S16) found that some boards helped executives to “make as full a use as possible of the different views and experiences” leading to better decisions. In a very different study focusing on case workers, Hwang and Han (2017) found that accountability pressures had a positive effect on cognitive dimensions, such as “talk,” “discussion,” and “gathering of more information” (see also Belardinelli et al, 2018; Kogan, 2017). Interestingly, recent studies also relate integrative decision-making by managers to the “negativity bias” in their strategic environment, stimulating improved decisions (Holm, 2018; Nielsen & Moynihan, 2017).…”
Section: Information Processingmentioning
confidence: 99%
“…Correspondingly, there has been a movement to balance compliance with a regulatory framework (i.e., performance) and an emphasis on professional commitment (i.e., accountability) (Casey Family Programs, 2011). The child welfare field entails a dynamic accountability and performance system (Hwang & Han, 2017). For instance, an emphasis on accountability derives from government (federal, state, and local), laws, policies, stakeholders, and citizens.…”
Section: Introductionmentioning
confidence: 99%
“…Not all empirical investigations find multiple accountabilities to be very problematic, however. In many instances, public sector actors have been found to develop strategic coping mechanisms to respond to the demands and expectations of their accountability forums, and have successfully integrated those into their workflow (Hwang, 2016;Hwang & Han, 2017;Schillemans, 2015;Schillemans & Bovens, 2011).…”
Section: Figure 11 Elements Of An Accountability Relationshipmentioning
confidence: 99%
“…Gregory, 1998;Romzek & Dubnick, 1987;Romzek & Ingraham, 2000), as well as accounts of experiences and strategies for coping with the accountability pressures of various individuals within the public sector (e.g. Ewert, 2020;Hwang & Han, 2017;Schillemans, 2015).…”
Section: Figure 11 Elements Of An Accountability Relationshipmentioning
confidence: 99%
See 1 more Smart Citation